Emotional intelligence, emotional labor, and job satisfaction among physicians in Greece - Psilopanagioti Aristea; Anagnostopoulos Fotios; Mourtou Efstratia; Niakas Dimitris (BMC, 2012)
Abstract Background There is increasing evidence that psychological constructs, such as emotional intelligence and emotional labor, play an important role in various organizational outcomes in service sector. Recently, in the "emotionally charged" healthcare field, emotional intelligence and emotional labor have both emerged as research tools, rather than just as theoretical concepts, influencing various organizational parameters including job satisfaction. The present study aimed at investigating the relationships, direct and/or indirect, between emotional intelligence, the surface acting component of emotional labor, and job satisfaction in medical staff working in tertiary healthcare. Methods Data were collected from 130 physicians in Greece, who completed a series of self-report questionnaires including: a) the Wong Law Emotional Intelligence Scale, which assessed the four dimensions of emotional intelligence, i.e. Self-Emotion Appraisal, Others' Emotion Appraisal, Use of Emotion, and Regulation of Emotion, b) the General Index of Job Satisfaction, and c) the Dutch Questionnaire on Emotional Labor (surface acting component). Results Emotional intelligence (Use of Emotion dimension) was significantly and positively correlated with job satisfaction (r=.42, p<.001), whereas a significant negative correlation between surface acting and job satisfaction was observed (r=−.39, p<.001). Furthermore, Self-Emotion Appraisal was negatively correlated with surface acting (r=−.20, p<.01). Self-Emotion Appraisal was found to influence job satisfaction both directly and indirectly through surface acting, while this indirect effect was moderated by gender. Apart from its mediating role, surface acting was also a moderator of the emotional intelligence-job satisfaction relationship. Hierarchical multiple regression analysis revealed that surface acting could predict job satisfaction over and above emotional intelligence dimensions. Conclusions The results of the present study may contribute to the better understanding of emotion-related parameters that affect the work process with a view to increasing the quality of service in the health sector.